Basic hydraulics - Industrial Training Zone (Lindon, Utah : Industrial Training Zone, 2002)
This video will enhance your employees' knowledge base with the most sophisticated hydraulic training available in the industry. Create the true learning atmosphere with 10-16 hours of instruction with this self paced, high retention, computer base program
System requirements: Windows - Pentium 166, Windows 95 or later, 16 MB available RAM, 4x CD-ROM, 16 bit color display ; Macintosh - Power PC, 16 MB available RAM, 4x CD-ROM, 16 bit color display
Keywords: Hydraulics